AN UNUSUAL CASE OF PAPILLARY THYROID CARCINOMA IODINE-131 AVID METASTASIS TO THE ADRENAL GLAND - Blažeković, Ivan (Acta Clin Croat, 2018)
SUMMARY – Papillary thyroid carcinoma (PTC) is considered one of the most favorable tumors, indolent, with rare distant dissemination. Lungs and bones are the most common metastatic sites. Unusual sites of PTC distant metastases are extremely rare. Brain, liver, skin, kidney, pancreas, and adrenal gland PTC metastases have been sporadically reported in the literature. An 86-year-old female patient underwent total thyroidectomy and neck dissection due to PTC. Postoperative whole body iodine-131 scintigraphy with I-131 SPECT/CT of the abdomen revealed radioiodne avid left adrenal gland metastasis together with high postoperative serum thyroglobulin (Tg) value of more than 5000 µg/L and high serum Tg antibodies. Considering the above-mentioned findings, patient‘s age and multiple comorbidities, radioiodine therapy was applied. PTC metastases to the adrenal gland are extremely rare, and to our knowledge, only nine cases have been reported in the literature. This case report complements rare examples of unusual PTC metastases.